An investigation of the effectiveness of cost cutting measures in the tourism and hospitality business: case of the Victoria Falls hotel - Dakwa, Japhet Nyasha (Midlands State University, 2018)
The study was carried out to analyse the effectiveness of cost cutting measures and problems hindering their effectiveness at The Victoria Falls Hotel. The need for the research emanated from the hotel increasing costs in the past years, there been variances between projected capital and operational costs and the actual costs. The research method used was a case study and questionnaires and interviews were used as primary data gathering instruments and financial statements were used as secondary data. The sample size used consisted of 31 respondents of which 28 responded to questionnaires and 3 responded to interviews. Tables were used to present data gathered, graphs, pie charts and bar charts were used to analyse data, and interviews were summarised. The major findings of the study showed that the hotel has not implemented all cost cutting measure to tackle the rising challenge, and these include lean approach, automation of systems and ABC system. The research recommended the implementation of the ABC costing and lean approach, automation of systems, use of LED lights and recycling of plastic materials it will significantly cut costs. The research further recommended introduction of involvement of employees in cost cutting measures and research and development in cost cutting measures as these were found to be hindering effectiveness of cost cutting measures.